Evaluation of polygalacturonase-inhibiting protein (PGIP)-mediated resistance against Verticillium dahliae, a fungal pathogen of potato - Berger, David Kenneth (University of Pretoria, 2013)
Dissertation (MSc (Plant Biotechnology))--University of Pretoria, 2006.